2003
DOI: 10.1165/rcmb.2002-0132oc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CD14 Blockade on Endotoxin-Induced Acute Lung Injury in Mice

Abstract: CD14 functions as a cell surface receptor for endotoxin (lipopolysaccharide [LPS]) and is thought to have an essential role in innate immune responses to infection. Previous studies have revealed attenuation of the systemic response after sepsis by blocking CD14. In this study, we tested the hypothesis that CD14 blockade protects against inflammatory responses associated with LPS pneumonia. We examined the effect of an anti-murine CD14 monoclonal antibody (4C1) on the development of acute lung injury induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 34 publications
4
30
0
Order By: Relevance
“…This amino acid substitution may disrupt IRAK4 signaling and result in a less-effective immune response to invading pathogens so that critically ill patients carrying the C/T/A clade have an increased risk of positive bacterial cultures. Our finding that the C/T/A haplotype clade of IRAK4 is associated with increased prevalence of positive bacterial cultures at admission to the ICU is consistent with our previous studies [36] , and with recent animal studies [37][38][39] which suggest that polymorphisms of innate immunity genes could be associated with impaired clearance of bacteria. A number of studies have shown that rare germline mutations in IRAK4 cause recurring bacterial infections in children and deficiencies in cytokine production in response to a range of microbial-derived TLR agonists and to recombinant IL-1 ␤ or IL-18 [10-13, 40, 41] .…”
Section: Discussionsupporting
confidence: 92%
“…This amino acid substitution may disrupt IRAK4 signaling and result in a less-effective immune response to invading pathogens so that critically ill patients carrying the C/T/A clade have an increased risk of positive bacterial cultures. Our finding that the C/T/A haplotype clade of IRAK4 is associated with increased prevalence of positive bacterial cultures at admission to the ICU is consistent with our previous studies [36] , and with recent animal studies [37][38][39] which suggest that polymorphisms of innate immunity genes could be associated with impaired clearance of bacteria. A number of studies have shown that rare germline mutations in IRAK4 cause recurring bacterial infections in children and deficiencies in cytokine production in response to a range of microbial-derived TLR agonists and to recombinant IL-1 ␤ or IL-18 [10-13, 40, 41] .…”
Section: Discussionsupporting
confidence: 92%
“…Intratracheal LPS induced lung injury with clear alveolar inflammation, characterized by intra-alveolar neutrophil infiltration and increased lavage fluid proinflammatory cytokines (TNF and MIP-2). There was also an increase in protein concentration in lavage fluid, indicating increased pulmonary endothelial and epithelial permeability, consistent with previous studies (6,30). Intravenous LPS induced lung injury of a predominantly vascular nature.…”
Section: Discussionsupporting
confidence: 91%
“…Perhaps the most prominent of these is the induction of both innate immune response and stress-related genes. These loci include the CD14 gene, which encodes the receptor for the complex of bacterial lipopolysaccharide (LPS) and LPS-binding protein, and has been recently and previously shown to be essential for the innate immune response to bacterial infection (53). The product of this gene has also been recently shown to mediate the innate immune response to gram-positive bacteria by binding to cell wallderived peptidoglycan-polysaccharide complexes, and this may explain its induction in response to B. anthracis (35).…”
Section: Resultsmentioning
confidence: 99%